Pengaruh Amelioran Formulasi terhadap Kualitas Tanah dan Air Kolam Gambut - Drastinawati '; Syafriadiman '; Saberina Hasibuan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted from February to April 2016 in the ponds of peatsoils at Jl. Petani Nenas Desa Kualu Nenas, Tambang, Kampar, Riau. Analysis of physical and chemical parameters have been done in Laboratory of Environment Quality Aquaculture (EQA), Fisheries and Marine Sciences Faculty, Riau University. Methods of experiment in this researchused with completely randomized design (CRD). Dose of ameliorant will be used as a factor in this research. 6 dose treatmentsare P0: without giving ameliorant, P1: 400 g / m2, P2: 600 g / m2, P3: 800 g / m2, P4: 1000 g / m2, P5: 1200 g / m2, and 3 replications. The results of this research that dose of ameliorant formulation has a very significant influence on weight volume (W/V) of soil, content of organic matter of soil and water turbidity of peat soil pond. The best treatment during the research was a dose of P1 (ameliorant formulation dose of 400 g/m2). Values obtained for the weight of the volume (W/V) of soil, soil organic matter content (KBOT), water temperature, water clarity, turbidity and pH on the treatment P1 are 0.62 g/cm3, 35.47%, 26-310C, 10.00 cm , 19.33 NTU and 5respectively.Keywords: Ameliorant, Peat, Physical and Chemical Parameters of the Peat Soil Ponds